Innovation education programs: toward a conceptual framework. Issue 2 (6th May 2014) - Maritz, Alex; de Waal, Anton; Buse, Stephan; Herstatt, Cornelius; Lassen, Astrid; Maclachlan, Ross
Abstract : Purpose: – Innovation education has been identified as a key contributor to enhancing the innovative behavior of individuals, organizations and economies; yet very little literature exists on the development and assessment of innovation education programs (IEPs). This is particularly so in the higher education and vocational education domains. The purpose of this paper is to bridge the gap in the literature, by proposing a conceptual framework of a multi-dimensional IEP. Design/methodology/approach: – The paper employs a transparent and reproducible procedure and critical appraisal of the literature; coupled with emergent inquiry and case study implementation of a leading international IEP. Findings: – The study provides a framework by which innovation education facilitators may develop and evaluate their IEPs. The proposed framework provides a thematic appreciation of the multi-dimensional relationships between components. Research limitations/implications: – Limited within the context of this case study, geographical context and scant literature on IEPs and reproducible procedure. Originality/value: – The study provides a conceptual innovation education framework, based upon a successful international innovation management program.